Contraceptive use among HIV-infected women and men receiving antiretroviral therapy in Lusaka, Zambia: a cross-sectional survey - Hancock, Nancy L. (BMC Public Health, 2016)
BACKGROUND: Family planning (FP) is an essential health service and an important part of comprehensive HIV care. However, there is limited information about the contraceptive needs of people living with HIV in sub-Saharan Africa, which in turn has hampered efforts to expand and integrate FP services into existing HIV programs. METHODS: We performed a cross-sectional survey to determine FP prevalence and predictors among HIV-positive women and men attending 18 public antiretroviral therapy (ART) clinics in Lusaka, Zambia. Trained peer counselors administered the 10-question survey to those seeking care for five days at each of the target sites. RESULTS: From February to April 2014, we surveyed 7,046 HIV-infected patients receiving routine HIV services. Use of modern contraception was reported by 69 % of female ART patients and 79 % of male ART patients. However, highly effective contraceptive use and dual method use were low among women (38 and 25 %, respectively) and men (19 and 14 %, respectively). HIV disclosure status (adjusted odds ratio (AOR) = 4.91, 95 % confidence interval (CI) = 3.32–7.24 for women, AOR = 3.58, 95 % CI = 2.39–5.38 for men) and sexual activity in the last 6 months (AOR = 5.80, 95 % CI = 4.51–7.47 for women, AOR = 6.24, 95 % CI = 3.51–11.08 for men) were associated with modern contraceptive use in multivariable regression. Most respondents said they would access FP services if made available within ART clinic. CONCLUSIONS: While FP-ART integration may be a promising strategy for increasing FP service uptake, such services must focus on assessing sexual activity and advocating for dual method use to increase effective contraceptive use and prevent unintended pregnancies.